Bibliometric review of the impact of additive manufacturing on industrial modernization: a study applying the Consolidated Meta-Analytic Focus Theory - Lage, Alice Teixeira Lacerda; Santos, Isabella Carvalho dos; Duarte, Mariana Bravim; Cavalini, Luiz Felipe Píccoli; Gomes, Thiara Cezana (Brazilian Journal of Production Engineering, 2026)
This study analyzes the impact of Additive Manufacturing (AM) on industrial modernization and its integration into Industry 4.0. The methodology consisted of a bibliometric review based on the Consolidated Meta-Analytic Focus Theory (TEMAC), with data collected from the Scopus and Web of Science databases. The analysis identified relevant semantic terms and mapped co-authorship and citation networks, resulting in a selected portfolio of eight articles for in-depth thematic analysis. The results reveal that the technology goes beyond the prototyping phase, establishing sustainability as a central benefit, alongside reduced logistical costs and mass customization. However, high material costs and the absence of technical standardization remain significant bottlenecks. Trends indicate the development of new raw materials and the expansion of AM in strategic sectors such as aerospace, automotive, and healthcare.
Keywords: Additive Manufacturing; Industry 4.0; 3D printing; Sustainability; Industrial Modernization